Ecclesiastical Museum: the House of the Blessed Osanna Andreasi in Mantua - Angela Ghirardi; Rosanna Golinelli Berto (Intrecci d'arte, 2018)
The contribution focuses on the House of the Blessed Osanna Andreasi in Mantua, property of the Dominican Order and entrusted in management to the Dominican Laity (formerly Third Order), assisted by the Association for the Dominican Monuments of Mantua, founded in 1993 that much engages in the development of the House with important cultural initiatives. From long time it has become a place of worship and of artistic interest. In 1997, the House entered the circuit of the AMEI (Association of Italian Ecclesiastical Museums). The House has largely retained the architectural features of the late fifteenth century, has a garden with porch and preserves inside it very significant rooms and objects, closely related to the human story of Blessed Osanna, who lived in the House for a long time, more than thirty years, and she died there in 1505, at the age of 56.